0
$\begingroup$

Consider the linear recurrence relation $a_n = 4a_{n-1}-4a_{n-2}$. Find the solution of this recurrence relation for the initial conditions $a_0= 0$ and $a_1= 2$.


So I went through the motions and triangularized it got the answer $$a_n=1/2(2^n-2(2^n)a_1 - 4(2^n)a_o$$ But I know that that is wrong and the correct answer is $n*2^n$ But it just doesn't work for me. 4 -4 1 0 is the matrix I start with and I find it's eigenvalue to be only 2 and null space{(2 1)^t} so I extend it and to get the triangular matrix and come to the same answer you see above which is wrong.

$\endgroup$
1
$\begingroup$

You are solving $$a_n - 4a_{n-1} + 4a_{n-2}$$ and assuming $a_n = c^n$ you end up with $c^2 - 4c + 4 = 0$, so $c_\pm = 2$. Hence, indeed, the general solution would be $a_n = A2^n + Bn2^n$ and substitution of the initial conditions will determine the corresponding coefficients $A,B \in \mathbb{R}$.

$\endgroup$
1
$\begingroup$

Alternatively, express as: $$a_n-2a_{n-1}=2(a_{n-1}-2a_{n-2}).$$ Let $b_n=a_n-2a_{n-1}, b_1=2$. Then: $$b_n=2b_{n-1} \Rightarrow b_n=2^n.$$ So: $$a_n-2a_{n-1}=2^n.$$ Can you finish?

Hint: divide by $2^n$ and denote $c_n=\frac{a_n}{2^n}$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.